Including and Training Family Caregivers of Older Adults in Hospital Care: Facilitators and Barriers. Issue 1 (January 2020) - Fields, Beth; Rodakowski, Juleen; Leighton, Cassandra; Feiler, Connie; Minnier, Tami; James, A. Everette
Abstract : Background: Despite the role caregivers play in the delivery of care, the interactions and training methods used with caregivers during an inpatient stay are not clear. Purpose: The purpose was to examine interactions and training methods used with caregivers during hospital care. Methods: A mixed-methods case study was conducted. Observations were summarized and interviews were analyzed using thematic analysis. Results: The frequency of caregiver engagement varied at different points in the care process but was highest among observations during the stay care point. Providers were most commonly using written and verbal instructions to train caregivers. Three themes emerged from the interviews and were described to be both facilitators and barriers to caregiver involvement: experience, time, and relationship. Conclusions: High-quality person and family-centered care depends upon coordinated efforts among health care systems, providers, patients, and caregivers. Future caregiver initiatives should aim to decrease disengagement, increase assessment, and broaden the use of training methods. Abstract : Supplemental Digital Content is Available in the Text.